Supervisory written feedback in ELT practicum: exploring content, linguistic features, and perceptions of preservice teachers - Safaa M. Abdelhalim; Asma Abdullah Alsahil (Humanities & Social Sciences Communications)
Abstract Research in the field of practicum supervisory feedback in English Language Teaching (ELT) contexts has highlighted its valuable role as a resource for knowledge acquisition and professional development among preservice teachers. However, there remains a scarcity of research examining the content and linguistic features of supervisory written feedback (SWF) in both general ELT contexts and specifically within the Saudi Arabian context of ELT practicum. Addressing this gap, this mixed-methods study examined the content and linguistic features of SWF within the context of ELT practicum supervision in Saudi Arabia. It also examined whether preservice teachers’ perceptions aligned with the feedback they received. We considered data from 1,981 pieces of SWF collected from 27 ELT practicum supervisors, along with questionnaire responses from 84 preservice teachers and interview data from 13 participants. The analysis revealed some congruity between the level, focus, and wording of the SWF and preservice teachers’ perceptions of the feedback. Notably, the feedback primarily centers on task performance and tends to be evaluative in nature. Our research uniquely combines feedback analysis and student perceptions, highlighting the positive impact of cognitive linguistic features on preservice teachers’ development and emphasizing the importance of constructive comments and avoiding authoritative language to enhance self-esteem and receptiveness. Additionally, we underscore the influence of observation instruments, emphasizing the value of less structured forms for reflective exchanges in supervisory written feedback.